(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Silicophosphate ceramics of the composition A2Zr2SiP2O12 (A – Li, Na, K, Rb,Cs) were synthesized and investigated. The powder samples were obtained by sol-gel methodwith subsequent thermal treatment of the reaction mixtures. The hot pressing method was used to fabricate the monolithic ceramics. The samples were characterized by XRD (including thermal studies), IR-spectroscopy, scanning electron microscopy (SEM) and energy-dispersive X-ray microanalysis. The sintering process of the ceramic Na2Zr2SiP2O12, its thermal expansion and ionic conductivity were studied.